Sometimes I grumblesquinch - Vail, Rachel (Orchard Books, an imprint of Scholastic Inc., 2022)
Exploring the key social emotional skills needed to navigate complicated feelings, this sweet and touching story follows Katie Honors, a nice kid who isn't able to hold in her feelings about her brother, as she learns an important lesson.